Un atelier di scultori altomedievali: la ‘prima bottega di Ventimiglia’ e la sua area di attività, gli arredi lapidei della cattedrale e la loro ricostruzione - Beghelli, Michelle (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
A recent study of a sizeable group of Early Medieval sculpted fragments has allowed to recognize the work of the same sculpting-atelier in a number of locations between South-Eastern France and Northern Italy in the late 8th century. Some sites, however, also attest to the work of other groups of sculptors operating before and after: one of them is the cathedral of Ventimiglia (Liguria, Italy), where in all likelihood some decorated stone fragments are related to an early 8th-century-atelier. The reconstruction of the original structures allowed identification of an ambo and a chancel screen, while the systematic study of the finds suggests that the same sculptors worked also in a very near and a in relatively distant location, i.e. Sanremo (Liguria) and Stenico (Trentino Alto Adige), though uncertainty remains about their place of origin (Lombardy, North-Eastern Italy?).